Public Expectation on Strengthening Municipal Governance through Government Preparedness in the Public Service Delivery - Tiwari, Surendra Babu (Kalika Journal of Multidisciplinary Studies, 2023)
With the introduction of the federal government system in Nepal, two local level elections were held which increased the public expectations of citizens although the power sharing and decentralization system at federal state and local level and local level is relatively difficult. The Ministry of Federal Affair and General Administration (MOFAGA) under the Local Government Operation Act has developed a Local Government Institutional Self-Assessment (LISA) model to assess municipal governance. This study examined the preparedness of Pokhara Metropolitan City for addressing the expectations of the people in public service delivery especially with the application of the LISA model and identified the measures of preparedness for the responsive and accountable municipal government. The sample size was 149 individuals selected from three wards (ward 8 in urban, ward 27 is in semi-urban and ward 24 in the rural/periphery area) of PMC where the sample was collected at the 5% level of significance and 8% margin of error. The findings of the study suggested that the assessment of the expectation is the first step and government preparedness should be according to the public service delivery mechanisms so as to strengthen municipal governance in the municipality. The LISA model in municipalities is the baseline for strengthening the municipal governance. The study has been a useful assessment for the capacity development and technical backstopping at the one hand the public expectations at the other.